2009
DOI: 10.1007/s10803-009-0917-y
|View full text |Cite
|
Sign up to set email alerts
|

Brief Report: No Increase in Criminal Convictions in Hans Asperger’s Original Cohort

Abstract: Hans Asperger originally used the term "autistic psychopathy" to describe his patients on the autism spectrum, leading to a possible confusion with psychopathic disorder and delinquent behaviour. We conducted a penal register search for 177 former patients of Asperger's clinic with a childhood diagnosis of "autistic psychopathy" or features of the disorder in Austria. The mean percentage of registered convictions was similar to that in the general male population of Austria over the studied time period. A qual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
30
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(33 citation statements)
references
References 20 publications
2
30
1
Order By: Relevance
“…A follow-up study of 177 of Hans Asperger's original clinic cases (to mean age 42) suggests that outcome can be good in terms of both employment and relationships [29] . This follow-up also showed that ASD is not associated with higher rates of criminal conviction [30] , important in the face of media reports of possible Asperger syndrome in high-profile violent offenders.…”
Section: Adult Trajectories In Asdmentioning
confidence: 54%
“…A follow-up study of 177 of Hans Asperger's original clinic cases (to mean age 42) suggests that outcome can be good in terms of both employment and relationships [29] . This follow-up also showed that ASD is not associated with higher rates of criminal conviction [30] , important in the face of media reports of possible Asperger syndrome in high-profile violent offenders.…”
Section: Adult Trajectories In Asdmentioning
confidence: 54%
“…A number of follow-up studies have indicated that individuals with ASDs are no more likely to engage in violent criminal behaviour compared to the general population [5] and, in fact, some studies have indicated that they may actually be less likely [6,7]. Unfortunately, media and academic reporting of violent crimes committed by individuals with ASDs has fueled an unsubstantiated association between offending and ASD [8][9][10].…”
Section: Autism Spectrum Disorders (Asd) and Criminalitymentioning
confidence: 99%
“…However, despite media speculation, surveys suggest that individuals with ASDs may be no more likely than the general population to engage in violent crime, and in fact, may be less likely (Mouridsen, Rich, Isager, & Nedergaard, 2008;Woodbury-Smith, Clare, Holland, & Kearns, 2006). Hippler, Viding, Klicpera, and Happ e (2010) conducted a study of penal register data regarding Hans Asperger's original group of 177 patients, and found that the rate and nature of crimes committed by these individuals were no different from that of the general population. In case records spanning 22 years and 33 convictions, there were only three cases of bodily injury, one case of robbery and one case of violent and threatening behavior (Hippler et al, 2010).…”
mentioning
confidence: 99%
“…Hippler, Viding, Klicpera, and Happ e (2010) conducted a study of penal register data regarding Hans Asperger's original group of 177 patients, and found that the rate and nature of crimes committed by these individuals were no different from that of the general population. In case records spanning 22 years and 33 convictions, there were only three cases of bodily injury, one case of robbery and one case of violent and threatening behavior (Hippler et al, 2010). It is crucial that these important findings are stressed in any dissemination of research regarding neurodevelopmental conditions and violent crime in order to avoid stigmatizing an already vulnerable group.…”
mentioning
confidence: 99%